Rancang Bangun Aplikasi Media Pembelajaran Hukum Tajwid Hidayatus Sibyan Pada Pondok Pesantren Arri’ayah - Umi Sa'adah; , Nur Aini H; Nurmayanti Nurmayanti (Elkom : Jurnal Elektronika dan Komputer, 2024)
Based on the observations that have been made at the Arri’ayah Islamic Boarding School in Lembak Village, Lembak District,Muara Enim Regency, the problems found are. Teaching and learning activities that are less interactive, in learning the law of tajwid in hidayatus sibyan’s book, students are still difficlut to understandt the material and there needs to be other alternatives to help students understand the materia being studied, one alternative is the use of technology for education, namely by using learning media. Especially now that may students are not interested in learning to use books, they reason that learning to use book is boring which ultimately impacts on students’ lack of understanding of the material that has been presend, tharefore that researcher designed learning media for the law of tajwid hidayatus sibyan, so that students are more interested when study, in collecting data researchers used descriptive qualitativ methods including conducting interviews, direct observation, and literature study and are built using UML (Unifield Modelling Language).